Safety profile of clarithromycin in broilers after repeated oral administration - Awadallah, Hanady; Awidat, Shaban; Bennour, Emad; Elhafi, Giuma; El-Mahmoudy, Abubakr (International Journal of Biological Research, 2016)
The effects of repeated oral administration of clarithromycin (7.5 mg/Kg B.W., daily for 5 consecutive days) on blood parameters, clinico-chemical parameters and vital organ histology were evaluated in Ross broiler chickens. Twelve clinically healthy birds have been used in a parallel study design, where they have been randomly divided into two groups. The 1st group received a dose of 7.5 mg clarithromycin/Kg as intracrop bolus daily for 5 consecutive days after 6 h fasting; while the 2nd group received iso-saline and was kept as control. Blood samples were collected from all birds via the wing and metatarsal vein punctures on the 5th day for clinico-chemical and haematological examinations; and liver, kidneys and heart were dissected out for histopathological examination. Results revealed that repeated administration of clarithromycin caused significant increases in ALP, AST, ALT, CK, urea and creatinine levels, compared to those of control. Metabolic parameters exhibited significant decrease in albumin with consequent decrease in total protein and decreased albumin/globulin ratio. Lipid parameters remained unchanged, compared to control. Leuckogram revealed that total leuckocytic count was decreased as a result of the decreased number of lymphocytes and mid-sized cells. On the other hand, granulocytes number exhibited significant increase (granulocytosis) together with increased number of platelets (thrombocytosis); while erythrogram remained insignifi-cantly affected. Liver and kidney showed inflammatory cellular infiltrations associated with degenerative changes and haemorrhages. Although heart did not show inflammatory cellular infiltrations, yet breakage in some bundles was noted. These data indicate that although clarithromycin did not cause any clinical serious manifestations on the treated birds, yet laboratory analysis revealed some adverse effects on some organs as liver, kidney and heart as well as alterations in some clinic-chemical and hematological parameters; these findings should be taken in consideration during therapy with clarithromycin.